Professional nurses' perspectives of an ideal performance management process - Sibonelo Ndlovu; Neltjie C. van Wyk; Ronell Leech (AOSIS, 2024)
Background: A well-managed performance management process can significantly influence professional nurses' job satisfaction and improve patient outcomes. Conversely, ineffective management of the process can lead to demotivation of the nursing staff. Aim: This study aimed to understand professional nurses' perspectives on an ideal performance management process. Setting: The study was conducted in a designated hospital in South Africa owned by a private healthcare group. The study population consisted of professional nurses involved in a performance management cycle. Methods: A descriptive qualitative research design with an appreciative inquiry approach was employed. Participants were selected through purposive sampling. Five focus groups of five professional nurses each were used to conduct interviews. The interviews lasted between 60 min and 80 min. The number of interviews conducted provided sufficient data for data saturation. The data were analysed using thematic analysis and the 5-D model of appreciative inquiry. Results: Trusting relationships between management and professional nurses play an essential role in ensuring a tailored performance management process. Training of both professional nurses and managers, a sound reward system for high-performing employees, and a fair and transparent process that addresses challenges and promotes opportunities can promote a positive work environment. Conclusion: Professional nurses require support from their managers and top management. Involving professional nurses in the planning and implementation can ensure proper relationships exist and that constraints are appropriately addressed. Contribution: Implementing the findings can improve the competencies of both managers and professional nurses to maintain a positive performance management process.